Electronic and Structural Properties of 2, 3‐Naphthalimide in Open‐Shell Configurations Investigated by Pulse Radiolytic and Theoretical Approaches. Issue 14 (12th April 2021) - Zhuang, Bo; Tojo, Sachiko; Fujitsuka, Mamoru
Abstract: Structural characterization of radical ions and triplet excited states is usually challenging because of their high reactivity and corresponding short lifetime, but can be achieved by combining pulse radiolysis and time‐resolved spectroscopic techniques. Herein, we report the transient absorption and time‐resolved resonance Raman spectra of the radical anionic and the lowest triplet states of a fundamental aromatic imide compound, 2, 3‐naphthalimide, recorded during pulse radiolysis. Distinct spectral features are observed for these transient species, which are further explored in the context of theoretical calculations. We found that the molecular structures of 2, 3‐naphthalimide in open‐shell configurations are closely related to the spin density localised on the naphthyl and carbonyl regions, as well as the decrease in local aromaticity because of changes of electron configurations. In particular, our results demonstrate that although in the neutral ground state and the lowest triplet state 2, 3‐naphthalimide exists as a symmetric molecule, in its radical anionic state, the addition of an electron leads to a deformed structure with unusual in‐plane asymmetry. Abstract : Time‐resolved resonance Raman measurement during pulse radiolysis, together with density functional theory calculations, demonstrates that whereas in the lowest triplet state of 2, 3‐naphthalimide the reverse of spin does not alter the symmetry of the neutral ground‐state molecule, the 2, 3‐naphthalimide radical anion was found to exhibit a deformed structure with unusual in‐plane asymmetry upon the addition of an electron.